The Relationship Between Semen Production And Sexual Behavior In Madura And Bali Bulls - Nisa'us Sholikah; Dewi Masyitoh; Sri Susilowati (Jurnal Ternak, 2025)
The objective of this study was to examine the relationship between sexual behavior and semen production in Bali and Madura bulls. 4 Bali bulls and 4 Madura bulls were used in this observational study. Sexual behavior observation included the duration of libido, duration of ejaculation, and false mounting. Semen production variables observed were total sperm and total motile sperm. All of these observations were replicated 10 times. Results showed that there was a significant correlation (p<0.05) between duration of ejaculation and total sperm in Bali bulls with the regression equation of Y = 8874-302x and R2 = 0.12 (r = -0.34). Bali bulls also had a significant correlation (p<0.05) between duration of ejaculation and total motile sperm with the regression equation of Y = 6218-215.1x and R2 = 0.11 (r = -0.34). Madura bulls had a significant correlation (p<0.05) between duration of ejaculation and total motile sperm per ejaculate with the regression equation of Y = 1812+268x and R2 = 0.11 (r = 0.34). In conclusion, Bali bulls had undesirable correlated response for the duration of ejaculation toward total sperm and total motile sperm. While Madura bulls had desirable correlated response for the duration of ejaculation toward total motile sperm.